Metacognitive interpersonal therapy for personality disorders : a treatment manual - Dimaggio, Giancarlo; Montano, Antonella; Popolo, Raffaele; Salvatore, Giampaolo (London ; New York : Routledge, Taylor & Francis Group, 2015)
'Patients with personality disorders need targeted treatments which are able to deal with the specific aspects of the core pathology and to tackle the challenges they present to the treatment clinicians. Such patients, however, are often difficult to engage, are prone to ruptures in the therapeutic alliance, and have difficulty adhering to a manualized treatment. Giancarlo Dimaggio, Antonella Montano, Raffaele Popolo and Giampaolo Salvatore aim to change this, and have developed a practical and systematic manual for the clinician, using Metacognitive Interpersonal Therapy (MIT), and including detailed procedures for dealing with a range of personality disorders. The book is divided into two parts, Pathology, and Treatment, and provides precise instructions on how to move from the basic steps of forming an alliance, drafting a therapy contract and promoting self-reflections, to the more advanced steps of promoting change and helping the patient move toward health and adaptation. With clinical examples, summaries of therapies, and excerpts of session transcripts, Metacognitive Interpersonal Therapy for Personality Disorders will be welcomed by psychotherapists, clinical psychologists and other mental health professionals involved in the treatment of personality disorders'--
Includes bibliographical references (pages 243-260) and index.
Keywords: Personality disorders -- Treatment; Metacognition